مسالك التحرير اللغوي: نصوص الجامعة الإسلامية العالمية بماليزيا للنشر أنموذجاً - Nasir Yusof; Zalika Adam (Department of Arabic IIUM, 2024)
This paper focuses in the nature of Arabic manuscripts submitted by the academics and researchers to the Research Management Centre of the International Islamic University Malaysia (IIUM) and in particular to the Publishing Unit of IIUM Press. These are works which range from good quality to the ones that need further refinement that necessitates the existence of an Arabic editor at the center. In this light, this study looks into the processes of language editing by outlining the characteristics of a language editor who scrutinizes the Arabic text to take on its challenges and find solutions for it with the purpose of producing the best quality for the Arabic readers. Among the conclusions of the study: that the editor would feel disappointed when the expected cooperation from the writer is not forthcoming due the reasons such as utter indifference, or abandonment or inferiority complex or lack of confidence or an assumed academic position or competence that would make the writer feel that they need no one other than themselves. On the other hand, a good writer would always feel elated to see his work to come out in a new design after the corrections and amendments in addition to the efforts by him in reading the edited texts more than once.